Case report: Bilateral damage to the immature optic radiation and secondary massive loss of retinal ganglion cells causing tunnel vision - Nilsson, Maria; Lennartsson, Finn; Öhnell, Hanna Maria; Gränse, Lotta; Jacobson, Lena (Frontiers in Neuroscience, 2023)
We describe the case of a 30-year-old woman, who needed a formal report on her visual impairment to seek support from society. She was born preterm, and during her neonatal period she suffered from bilateral intraventricular hemorrhage (IVH) grade 3; a condition which may cause cerebral visual impairment (CVI) because of damage to the retro-geniculate visual pathways. Individuals with such brain damage of this severity are often restricted by cerebral palsy (CP) and intellectual disability and therefore commonly have limited ability to cooperate in the assessment of visual function. However, our patient was capable of providing reliable test results and she manifested only a small island of central vision in each eye with additional reduced visual acuities. She cooperated well in examinations with magnetic resonance imaging of the brain, with optical coherence tomography (OCT) of the retinal ganglion cells, and with multi-focal visual evoked potentials, each test providing information concerning potential limitations in the structural prerequisites for visual function. What makes our case unique is the severity of damage to the optic radiations and the massive secondary loss of most of her retinal ganglion cells (GC). Yet there is some measurable visual function, possibly on account of developmental neuroplasticity during early development where surviving GCs give priority to the central visual field. Despite her visual difficulties, she is a keen portrait painter. Our patient may be representative of, and a spokesperson for, other individuals with extensive brain damage of the same etiology, who are unable to perform perimetric tests and therefore run the risk of not being recognized as severely visually impaired, and consequently, not being given the best conditions for habilitation. OCT may serve as a helpful diagnostic tool. Aim To describe visual behavior and practically applied visual function in relation to structural prerequisites for visual function.